Prevalence and Diversity among Anaplasma phagocytophilum Strains Originating from Ixodes ricinus Ticks from Northwest Norway. (24th August 2014) - Tveten, Ann-Kristin
Abstract : The tick-borne pathogen Anaplasma phagocytophilum causes great concern for livestock farmers. Tick-borne fever is a widespread disease in Norway, and antibodies have been produced amongst sheep, roe deer, red deer, and moose. The main vector Ixodes ricinus is found along the Norwegian coastline as far north as the Arctic Circle. A total number of 1804 I. ricinus ticks were collected and the prevalence of the pathogen was determined by species-specific qPCR. The overall infection rate varied from 2.83% to 3.32%, but there were no significant differences (p = 0.01 ) in the overall infection rate in 2010, 2011, or 2012. A multilocus sequencing analysis was performed to further characterise the isolates. The genotyping of 27 strains resulted in classification into 19 different sequences types (ST), none of which was found in the MLST database. The nucleotide diversity was for every locus <0.01, and the number of SNPs was between 1 and 2.8 per 100 bp. The majority of SNPs were synonymous. A goeBURST analysis demonstrated that the strains from northwest Norway cluster together with other Norwegian strains in the MLST database and the strains that are included in this study constitute clonal complexes (CC) 9, 10, and 11 in addition to the singleton.